Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.

Evaluating the influence of nature connection and values on conservation attitudes at a tropical deforestation frontier - Katarzyna M. Mikołajczak; Jos Barlow; Alexander C. Lees; Christopher D. Ives; Micha Strack; Oriana Trindade de Almeida; Agnis C. Souza; Frazer Sinclair; Luke Parry (Conservation Biology, 2023)
Inner phenomena, such as personal motivations for pursuing sustainability, may be critical levers for improving conservation outcomes. Most conservation research and policies, however, focus on external phenomena (e.g., ecological change or economic processes). We explored the factors shaping 9 conservation attitudes toward forest and wildlife protection among colonist farmers around an Amazonian deforestation frontier. Our data comprised 241 face‐to‐face quantitative surveys, complemented with qualitative insights from open‐ended questionnaire responses and opportunistic semistructured interviews. To account for the full spectrum of possible inner motivations, we employed measures of nature connection (indicating biospheric motivation) and personal values organized around the traditionalism (traditionalist through to high openness to change) and universalism dimensions (egoistic through to altruistic motivations). We used averaged beta‐binomial generalized linear models to assess the role of external factors (socioeconomic, sociodemographic, and environmental) and personal (inner) motivations on the variation in attitudes. Each attitude was modeled separately. The relative importance of each predictor was judged by the proportion of models where it appeared as significant. Proconservation views were expressed by the majority (at least 65%) of the respondents in 7 out of the 9 attitude models. The most consistent predictors were emotional nature connection and personal values (significant in 4–6 out of 9 models), rather than external phenomena (significant in 0–5 models). However, the poorest farmers had lower scores on the agreement with prioritizing nature over development (𝛽 = –0.52, 95% CI: –0.96 to –0.07). Qualitative data also indicated that economic barriers hinder forest conservation on farms. These results suggest that biospheric, traditionalistic, and altruistic motivations promote people's proconservation attitudes, but nurturing these latent motivations is unlikely to improve conservation outcomes if material poverty remains unaddressed. Integrating the inner–outer perspective into conservation thinking and practical interventions could foster environmental stewardship and increase human well‐being.

The role of waterborne carbon in the greenhouse gas balance of drained and re-wetted peatlands - Chris D. Evans; Flo Renou-Wilson; Maria Strack (Aquatic Sciences, 2016)

Cre-mediated seed-specific transgene excision in tobacco - L. Kopertekh; K. Schulze; A. Frolov; D. Strack; I. Broer; J. Schiemann (Plant Molecular Biology, 2010)

Detoxification of ferulic acid by ectomycorrhizal fungi - B. Münzenberger; E. Hammer; V. Wray; F. Schauer; J Schmidt; D. Strack (Mycorrhiza, 2003)

Internal audit for a publicly owned treatment works enforcement response plan - Geoffrey D. Strack; Paul L. Bishop (Clean Technologies and Environmental Policy, 2002)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Accumulation of secondary compounds in barley and wheat roots in response to inoculation with an arbuscular mycorrhizal fungus and co-inoculation with rhizosphere bacteria - Thomas Fester; Walter Maier; D. Strack (Mycorrhiza, 1999)